Cost Analysis Approach of Providing Antiretroviral Therapy Services to HIV-Infected Patients at Public Health Centres in Dar es Salaam, Tanzania - Godfather D. Kimaro; Christian Bottomley; Lorna Guinness; Sokoine Kivuyo; Shabbar Jaffar; Godfrey S. Mfinanga (Current Innovations in Disease and Health Research Vol. 9, 2023)
Healthcare strategy planning requires an understanding of the costs to enhance the efficiency of the approach. Since 2003, just four published HIV costing studies from low-income sub-Saharan Africa have used an individual-level micro-costing approach, but all were retrospective. This chapter primarily focuses on developing a cost analysis for offering antiretroviral therapy services to HIV patients. The REMSTART trial was implemented in Dar es Salaam, Tanzania, and Lusaka, Zambia and the cost study was restricted to Tanzania. The study developed screening for cryptococcal meningitis and tuberculosis and a short initial period of home-based adherence support for patients initiating ART with advanced HIV disease in Tanzania and Zambia. We estimated costs of providing routine HIV care by using a micro-costing approach. Incremental costs for the different novel components of service delivery were also estimated. The findings revealed that 434 people were enrolled in the intervention arm and 436 in the standard care/control arm out of the 870 people in Tanzania. At enrollment, the median (IQR) participants’ CD4 cell count was 52 (20, 89) cells/mm3 and their median (IQR) age was 38 (31, 44) years. ART drugs, clinic visits and hospital admission constituted 50%, 19%, and 19% of the total cost per patient year, while diagnostic tests and non-ART drugs (co-tri-moxazole) accounted for 10% and 2% of total per patient year costs. The incremental costs of the intervention to the health service over the first three months was US 59 (p<0.001; 95%CI 52–67) and over a one year period was US 67(p<0.001; 95%CI 50–83). This is equivalent to an increase of 55% (95%CI 51%–59%) in the mean cost of care over the first three months, and 25% (95%CI 20%–30%) increase over one year of follow up. This study concluded that Micro-costing approaches provide a way to obtain an in-depth understanding of cost structures and cost variation between individuals as well as over time.